Root response in Pisum sativum and Zea mays under fluoranthene stress: morphological and anatomical traits - Kummerová, Marie; Zezulka, Štěpán; Babula, Petr; Váňová, Lucie (Chemosphere, 2013)
Introduced organic pollutants in all ecosystem compartments can cause stress resulting in a wide range of responses including different root development. In this study, the effects of a polycyclic aromatic hydrocarbon-fluoranthene (FLT; 0.1, 1 and 7 mg L(-1)) on the growth, morphology and anatomical structure of roots of pea and maize was evaluated. In comparison with pea, significant stimulation of root system growth of maize caused by 0.1 mg L(-1) (total length longer by 25%, number of lateral roots by 35%) and its reduction (total length by 34%) already by 1 mg L(-1) FLT is the proof of different interspecies sensitivity to low and higher environmental loading. Nevertheless in both plant species a high loading 7 mg L(-1) FLT significantly reduced both growth (total length by 95% in pea, 94% in maize) and the number of lateral roots (by 78% in pea, 94% in maize). Significantly increased thickness of root of both maize and pea was caused by 7 mg L(-1) FLT and in maize already by 0.1 mg L(-1) FLT. It may be mainly connected with an enlargement of stele area (up to 50% in pea and 25% in maize). Increased xylem area in root tip (by up to 385% in pea, 167% in maize) and zone of maturation (up to 584% in pea, 70% in maize) and its higher portion in stele area of root tip (by 9% in pea, 21% in maize), mainly in roots exposed 7 mg L(-1) FLT, are a proof of an early differentiation of vascular tissue and a shortening of root elongation zone. Moreover in both plant species exposed to this treatment, the decline of rhizodermis cells and external layers of primary cortex was found and also significant deformation of primordia of lateral roots was recorded.
Keywords: Zea mays; Stress, Physiological; Soil Pollutants; látky znečišťující půdu; fyziologický stres; hrách setý; kukuřice setá; fluoreny; Plant Roots; kořeny rostlin; Pisum sativum; Fluorenes